Evaluation of tuberculosis associated chronic pulmonary disease at community health care: a case control study - Sharma, Chandan; Badyal, Ashima (International Journal Of Community Medicine And Public Health, 2021)
Background: Chronic obstructive pulmonary disease (COPD) is known to occur in patients with previous history of pulmonary TB. It is still not very well known if there is any difference of clinical presentation between smoking related COPD or/and TB associated COPD. Methods: The present case control study was conducted at CHC Katra, Department of Medicine, over a period of 6 months from August 2018 to February 2018, on 100 patients; 50 suffering from COPD and 50 healthy individuals. Detailed clinical history for duration of symptoms, previous hospitalizations, and exposure to smoking along with the history of TB and ATT courses was recorded. Results: History of TB was found in 17 patients among cases and 7 patients among controls. In TB associated COPD, the pack years of smoking in case of smokers was 22.4±19.2. 44% (15/34) having exposure to smoking had history of TB. Mean age of patients exposed to smoking was (53.3±7.4) and that of non-smokers (60.1±8.2). A positive correlation with age, BMI, and duration of symptoms was found. Our results showed that almost one-third of COPD patients (34%) had history of TB. TB-associated COPD patients had similar symptoms in our study except for high frequency of hemoptysis. Conclusions: A detailed population survey is needed on COPD patients with history of TB. A larger group study among never-smokers is also needed. Finally, it is concluded that the case burden of TB associated COPD is real, huge and an urgent policy decision in this regard is mandated.